PENENTUAN JUMLAH TENAGA KERJA OPTIMAL DENGAN PENDEKATAN WORKLOAD ANALYSIS (STUDI KASUS DI PB. SRI TANI) - Yunanta, Arrijal Luthfia; Darajatun, Rizki Achmad; -, Kusnadi (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2021)
PB. Sri Tani is one of the Rice Milling located in Banyusari, Karawang. In the production process, the owners still did not know the standard time, the number of workers used, and the proper job description based on the number of optimal workers. The purposes of this study were to find out what is the standard time using the stopwatch time study method, rating factor, allowance and to determine the number of optimal workers use the workload analysis approach, then distribute the job description based on the number of optimal workers. As for, based on the results of research and calculations using the stopwatch time study method, it was known that the time to process a sack of rice was 3.17 minutes and to produce 6 tons (120 sacks) it took 380.4 minutes or 6.3 hours. The number of optimal workers based on the work load analysis (WLA) method was 5 people that it was using 6 people previously, and then it can save the salary payments Rp. 1,100,000 per month. In addition, it has been proposed that the work positions and job descriptions for 5 workers.